Pengaruh Disiplin Kerja dan Kompensasi Terhadap Kinerja Karyawan Pada UD. Karya Mandiri Di Kecamatan Makale Utara Kabupaten Tana Toraja - Tangkeallo, Dian Intan; Salomba, Sriyanti (Jurnal Ekonomi, Bisnis dan Terapan (JESIT), 2021)
The purpose of this study is to determine whether there is an effect of compensation and work discipline on employee performance at UD. Karya Mandiri in Makale Utara, Kabupaten Tana Toraja. The total population is 31 people, all of whom are respondents in this study. This study uses primary data obtained by distributing questionnaires to employees who work at UD. Karya Mandiri in Makale Utara, Kabupaten Tana Toraja. The data analysis technique used in this study is multiple linear regression, which is operated through the SPSS 23 program. The results show that work discipline (X1) has a positive and significant effect on employee performance (Y) at UD. Karya Mandiri in North Makale District, Tana Toraja Regency. While compensation (X2) has a positive and significant effect on employee performance (Y) at UD. Karya Mandiri in North Makale District, Tana Toraja Regency. Simultaneously work discipline and compensation have a positive and significant effect on employee performance at UD. Karya Mandiri in Makale Utara, Kabupaten Tana Toraja.